Youth, Inequality and Social Change in the Global South - Cuervo, Hernan; Miranda, Ana (Perspectives on Children and Young People, 2019)
This book gathers international and interdisciplinary work on youth studies from the Global South, exploring issues such as continuity and change in youth transitions from education to work; contemporary debates on the impact of mobility, marginalization and violence on young lives; how digital technologies shape youth experiences; and how different institutions, cultures and structures generate a diversity of experiences of what it means to be young. The book is divided into four broad thematic sections: (a) Education, work and social structure; (b) Identity and belonging; (c) Place, mobilities and marginalization; and (d) Power, social conflict and new forms of political participation of youth.